Does cost sharing really reduce inappropriate prescriptions? - Joan Costa-i-Font; Marin Gemmill-Toyama (Center for Economic Studies and ifo Institute (CESifo), 2010)
This paper explores different empirical strategies to examine the effect of cost sharing for prescription drugs in some dimensions of medication-related quality, namely the probability of inappropriate prescription drug use among United States seniors. Using data from 1996 to 2005, we explore various specifications that correct for sample selection, endogeneity, and unobserved heterogeneity. We find a small, but measurable, negative price elasticity for inappropriate drug use with respect to self-reported average out-of-pocket costs for all drugs consumed. That is, user fees reduce the use of potentially inappropriate medications, however the elasticity of cost sharing is lower than that of drugs in general and the price elasticity is relatively close to zero, suggesting that any quality improvements from co-payments are small.
Keywords: I18; I10; 330; Pharmazeutisches Produkt; Konsumentenverhalten; Selbstbeteiligung (Versicherung); Produktqualität; USA